Aplikasi Pengurusan Fazira Car Wash Menggunakan Android (Fazira2Clean) - Mohd Othman, Azni; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2021)
Fazira Car Wash Management Application Using Android (Fazira2Clean) is an Android -based mobile application that works to manage and perform car wash reservations more systematically and managed and aims to improve weaknesses in existing reservation management methods. The prototype model was used as a methodology to give developers the flexibility to complete Android Studio with the Java programming language, and the Firebase database was chosen as the application development tool. The project is also developed based on an object -oriented approach illustrated through applied case diagrams, sequence diagrams, activity diagrams as well as class diagrams. Generally, this application is developed to assist in booking management and related reports to increase the effectiveness and efficiency in booking management through interactive implementation between the system interface, database, and user communication.